Perancangan dan Implementasi Website Sistem Antrian Bank Berbasis Queue untuk Efisiensi Pelayanan Nasabah - Dinanti, Augis; Muchtar, Irfan Zaky; Gultom, Jonatan Rio; Hutabarat, Aldrik Bastio (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study designs and implements Bank Jali, a web-based bank queue system that applies a queue data structure with the First In First Out (FIFO) principle to improve service efficiency. The research and development method includes requirement analysis, design, implementation, testing, and evaluation. The application is built with HTML, CSS, and JavaScript, storing queue data temporarily through localStorage so the entire process runs client-side without a dedicated server. Key features include online queue registration, digital ticket generation, real-time status monitoring with waiting-time estimation, and an admin dashboard for managing teller and customer service queues. Testing shows the system operates reliably, processes queues according to FIFO, and provides a practical, lightweight user experience across devices.